Stakeholders' awareness and perception towards graphic health warning, opportunities and challenges for tobacco control policy in Nepal: A qualitative study. - Netra Lal Aryal; Binita Kumari Paudel; Babu Ram Pokhrel; Sushila Acharya; Saraswati Bhandari; Sheetal Bhandari; Manish Rajbanshi; Shalik Ram Dhital (PLOS Global Public Health)
Despite the efforts of the Government of Nepal, including the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC), including 90% of health risk warnings on tobacco packets, the prevalence rate of tobacco consumption and its mortality and morbidity remain a challenge. This study aimed to explore awareness and perception towards Graphic Health Warning (GHWs), challenges, and opportunities for tobacco control policies among stakeholders in Galyang Municipality of Syjanga district, Nepal.This study employed a qualitative study design among 11 stakeholders of the Galyang municipality. Key Informant Interviews (KII) were conducted using the KII guideline. A purposive sampling technique was used to select study participants. The study adhered to the Consolidated Criteria for Reporting Qualitative Studies (COREQ) guideline. Thematic analysis was performed for data analysis.Participants, including Mayors, Ward Chairpersons, Health Officials, and community leaders, generally recognized GHWs as effective in raising awareness but noted their limited impact on altering smoking behavior, particularly among dependent smokers. While GHWs were seen as more effective than text warnings, many participants emphasized the need for stronger policy enforcement, including restrictions on tobacco sales and smoking in public places. Cleared, high-contrast images on cigarette packets, comprehensive public awareness programs, and active engagement of political leaders and stakeholders to strengthen tobacco control policies and implementation. This study found that GHWs raise awareness about the harms of tobacco, but their impact on behavior change, particularly among dependent smokers, remains limited. Key challenges include weak enforcement of tobacco control policies, regulatory gaps, and limited government engagement. A multi-sectoral approach with community leaders, political commitment, school-based intervention, stronger local governance, licensed tobacco shops, and enhanced GHWs is vital for effective tobacco control. Effective policy execution and community involvement were highlighted as critical to the success of tobacco control initiatives.